Metal Additive Manufacturing for early concept Validation - Nordström, Nils Emil Fredrik (My University, 2024)
The manufacture of prototypes using metal additive manufacturing (AM) has been used for many years, however, there has been little research on how to heat treat AM aluminum parts to match the properties of parts manufactured using high pressure die casting (HPDC). Prototypes made using sand casting can only reach 70% of the strength of production HPDC parts, which is not ideal for early testing. As printed, the strength of AM aluminum alloys manufactured with Powder Bed Fusion – Laser Beam (PBF-LB) is much higher than HPDC aluminum alloy. Hence, AM parts can be heat treated to reduce their strength until it matches that of HPDC parts. This research investigated how the heat treatment of AM aluminum alloy AlSi10Mg affects its hardness, yield strength, ductility, and microstructure, as well as the mechanisms that cause the changes in properties. In addition, a replica of a production HPDC part was manufactured using AM to develop a prototype manufacturing process and to compare the results between them. The results showed that heat treating AM parts at 325ºC for 4 hours produced the closest yield strength to that of HPDC parts. However, the ductility was much greater for the AM parts due to differences in alloying elements and microstructure. For making an AM demonstrator, the process developed was to manufacture the part with PBF-LB along with some tensile bars, heat treat the part on the build plate, machine any critical surfaces, remove the support material, and treat the surface with glass blasting to remove any remaining particles/powder on the surface.
Keywords: Additive manufacturing; Powder Bed Fusion – Laser Beam (PBF-LB); High pressure die casting; Aluminum alloy AlSi10Mg; Heat treatment; Material characterization; Hardness; Tensile strength; Microstructure